172k views
4 votes
Solve (x + 3)2 + (x + 3) – 2 = 0.
Let u =?

A. X
B. x+3
C. (x+3)^2

User Matt Clark
by
6.3k points

2 Answers

1 vote
If you let u = x+3, then the equation updates to a more simpler form: u^2+u-2 = 0

The final answer is choice B
User Santosh Shinde
by
5.8k points
7 votes

Answer with explanation:

The expression which we have to solve is :

(x+3)²+(x+3)-2=0

⇒This is Quadratic expression which has two roots.

To solve this, Suppose, x+3=u

The above expression reduces to

⇒u²+u-2=0

⇒u²+2 u-u-2=0

⇒u×(u+2)-1×(u+2)=0

⇒(u-1)(u+2)=0

⇒u-1=0 ∧ u+2=0

⇒u=1 ∧ u=-2

⇒x+3= 1 ∧ x+3 = -2

⇒x=1-3 ∧ x= -2-3

x= -2 ∧ x=-5

u=x+3

Option B

User Al Mahdi
by
6.1k points